The weapons of Bonnie Prince Charlie – a new examination. (2nd January 2020) - Corp, Edward; Rimer, Graeme
Abstract : It is well documented that the Jacobite 3rd Duke of Perth gave Prince Charles Stuart, then in Rome, some Highland weapons and armour in 1739. Two swords and a targe in Scottish collections have been traditionally described as possibly forming part of that gift, but a different sword has recently been identified as a more likely candidate to be the one given by Perth to the prince. A re-examination both of the available documentary evidence and of the weapons themselves demonstrates that neither the two swords nor the targe in Scotland, nor a similar targe at Warwick Castle, could possibly have been given to Prince Charles Stuart in 1739, whereas it now seems probable that the recently identified sword really was the one given to him by the Duke of Perth.